Embrace our senses - Ahmad Izuddin, Sarah Raihani; Mohd Khairul Anuar, Khairunnisa Najwa; Muzamir, Iwana Farhani; Zuad Firdaus, Muhammad Harith Farhan; Abdul Aziz, Muhammad Amirul Najmi; Hirnizan, Nur Hazwani Afifah; Ismawi, Hidayatul Radziah (Malaysian Integrated Medical Professionals Association (MIMPA), 2024)
This e-book is based on the topic: Embrace our Senses. Each of the five senses will be discussed as well as the 6th sense. It is hoped that this book will encourage a newfound appreaciation for our senses.